Hematology Profile of Pregnant Women in Trimester III with Covid-19 - Ririn Handayani; Ernawati Anggareni; Nazmi Kamila (Journal of Ners and Midwifery, 2022)
Women pregnant  classified  as  vulnerable  groups  because  of  changes  in  body  physiology  and  immune  response  mechanisms  in  their  bodies.  SARS-CoV-2  infection  in  pregnancy  stimulates  an  increase  in  the  expression  of  proinflammatory  cytokines,  namely  IL-6,  IL-12,  IL-1β, dan IFNγ which  can  damage  lung  organs.  The  purpose  of  this  study  was  to  look  at  the  hematological  profile  of  pregnant  women  with  COVID-19,  especially  in  the  third  trimester  as  an  effort  to  detect  the  severity  of  the  infection  experienced  by  the  mother.  This  study  was  a  quantitative  descriptive  study  with  a  retrospective  design  using  secondary  data  from  medical  records.  This  study  was  carried  out  at  dr.  Soebandi  Hospital  Jember,  medical  record  data  were  taken  from  January to  December  2021.  The  subjects  of  study  were  pregnant  women  in  the  third  trimester  with  COVID-19.  The  sampling  technique    total  sampling.  Method  of  analysis  in  this  study  used  a  frequency  distribution.  Results  of  the  study  showed  that  100%  of  pregnant  women  with  COVID-19  had  symptoms  of  cough,  runny  nose,  fever  and  shortness  of  breath.  Results  of  the  mother's  hematological  examination  showed  an  increase  in  leukocytes  (48%)  and  a  decrease  in  lymphocytes  (92%),  most  of  the  mothers  had  anemia  (76%),  there  was  a  decrease  in  platelets  (8%)  and  an  increase  in  platelets  (20%). In conclusion, they had  the  same  symptoms  as  patients  in  general,  including  cough,  runny  nose,  fever  to  shortness  of  breath,  an  increase  in  leukocytes  and  a  decrease  in  lymphocytes,  most  of  the  mothers  also  experience  anemia and  changes  to  abnormal  maternal  platelets  occur.